The Role of Supply Chain Resilience in Enhancing Operational Efficiency among Manufacturing SMEs - Nugroho, Arif; Santosa, Budi; Khoa, Tran Minh (Journal of Economics and Management, 2025)
This study explores the critical role of supply chain resilience (SCR) in improving operational efficiency among manufacturing small and medium-sized enterprises (SMEs). In today’s volatile business environment, disruptions such as global pandemics, geopolitical tensions, and raw material shortages have underscored the need for resilient supply chains. Drawing on empirical data collected from manufacturing SMEs, this research identifies key dimensions of SCR namely flexibility, responsiveness, and risk management and examines their impact on cost efficiency, production continuity, and delivery performance. The findings indicate that firms with higher supply chain resilience are better equipped to sustain operations during disruptions, adapt to market changes, and maintain competitiveness. This study contributes to the growing body of knowledge on supply chain management by highlighting the strategic importance of resilience as a driver of operational excellence in SMEs. Recommendations are provided for SME managers to strengthen their supply chain structures and build capabilities that ensure long-term efficiency and sustainability.